Origin story : a big history of everything - Christian, David, 1946- (New York : Little, Brown and Company, 2018)
Studies the whole of history, from the Big Bang to the present and into the future, to explore the place of human beings in the universe, discussing defining events, major trends, and human origins to reveal the hidden threads that tie everything together.
Keywords: Civilization -- Philosophy; Cosmology; World history; Human evolution; Biocomplexity; Civilization -- Philosophy; Cosmology; World history; Evolution; Biodiversity